2009
DOI: 10.1080/14786410802497240
|View full text |Cite
|
Sign up to set email alerts
|

A novel 1-indanone isolated from Uvaria afzelii roots

Abstract: Bioactivity-guided fractionations of chloromethylenic extract of the roots of U. afzelii (Annonaceae), using Leishmania donovani and Trypanosoma brucei brucei bioassay, resulted in the isolation of the two known compounds, emorydone (1) and demethoxymatteucinol (2), previously isolated from the stems, which were characterised from this source. In addition, the novel 1-indanone, afzeliindanone (3), was also isolated. The structure determination of afzeliindanone (3) was elucidated on the basis of spectral data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…Spodoptera larval frass, which deters oviposition in conspecific females, contains 1-indanone (Klein et al, 1990;Anderson et al, 1993), but we were unable to corroborate presence of 1-indanone or any other indane in frass collections of S. littoralis reared on several diets (data not shown). Indanone is found in roots of tropical plants (Okpekon et al, 2009), decaying wood fungi (Rukachaisirikul et al, 2013), and filamentous marine cyanobacteria (Nagle et al, 2000), which are probably not relevant for S. littoralis or C. pomonella. However, our results indicate that one or several indanone analogs are ligands for CpomOR19 and SlitOR19, but the source of these compounds and their behavioral and ecological roles are yet to be elucidated.…”
Section: The Ecological Role Of Indanes Is Yet Unknownmentioning
confidence: 99%
“…Spodoptera larval frass, which deters oviposition in conspecific females, contains 1-indanone (Klein et al, 1990;Anderson et al, 1993), but we were unable to corroborate presence of 1-indanone or any other indane in frass collections of S. littoralis reared on several diets (data not shown). Indanone is found in roots of tropical plants (Okpekon et al, 2009), decaying wood fungi (Rukachaisirikul et al, 2013), and filamentous marine cyanobacteria (Nagle et al, 2000), which are probably not relevant for S. littoralis or C. pomonella. However, our results indicate that one or several indanone analogs are ligands for CpomOR19 and SlitOR19, but the source of these compounds and their behavioral and ecological roles are yet to be elucidated.…”
Section: The Ecological Role Of Indanes Is Yet Unknownmentioning
confidence: 99%
“…In this study, it was reported that the methanolic extracts of the root of Uvaria afzelii, at doses of 125 mg/kg, 250 mg/kg and 500 mg/kg, significantly reduced the serum hepatic enzymes, total and un-conjugated bilirubin. Phytochemical studies of this plant has shown the presence of syncarpic acid, dimethoxym atteucinol, emorydone, 2-hydroxydemethoxym at-teucinol, uvafzelic acid, syncarpurea, afzeliindanone, flavonoids, triterpenoids and phenols [76][77][78]. Some of these compounds have also been credited for their antiparasitic and antioxidant activities [79].…”
Section: Uvaria Afzeliimentioning
confidence: 99%
“…These compounds are renowned for their “non-host” origins (Klein et al, 1990; Anderson et al, 1993; Nagle et al, 2000; Okpekon et al, 2009; Rukachaisirikul et al, 2013). CpomOR19 binding to indanes represented the first deorphanization of a receptor of the codling moth to compounds emitted by non-hosts.…”
Section: Functional Characterization Of Cpomor19mentioning
confidence: 99%